Foreign Direct Investment and Environmental Degradation: Further Evidence from Brazil and Singapore - KOSTAKIS, Ioannis; LOLOS, Sarantis; SARDIANOU, Eleni (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017DO - 10.14505//jemt.v8.1(17).04, 2017)
This paper assesses empirically the role of foreign direct investment (FDI) inflows on environmental quality, measured by CO2 emissions. The cases of Brazil and Singapore are taken as examples for our empirical investigation, on the grounds of their specific similarities and differences. The empirical analysis is carried out in a multivariate setting, using a variety of models (ARDL, FMOLS, and OLS) for the early 1970s to 2010. The results indicate that FDI inflows have lead to environmental degradation in Brazil but not in Singapore. Our findings point to the importance of the sectorial composition of FDI as a determinant of its impact on environmental quality. The analysis is supplemented with an environmental Kuznets curve (EKC), our results showing that the EKC hypothesis holds for the case of Singapore but its validity is marginal in Brazil.